2009
DOI: 10.1080/09540090902733780
|View full text |Cite
|
Sign up to set email alerts
|

Genre classification using chords and stochastic language models

Abstract: Music genre meta-data is of paramount importance for the organization of music repositories. People use genre in a natural way when entering a music store or looking into music collections. Automatic genre classification has become a popular topic in music information retrieval research both with digital audio and symbolic data. This work focuses on the symbolic approach, bringing to music cognition some technologies, like the stochastic language models, already successfully applied to text categorization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Since the amount of digitized music has increased enormously over the past years, the need for tools to organize, order and cluster music has increased as well. Automatic music classification has already been investigated on the basis of many different ideas, among others compression distance [2], Hidden Markov Models [1], stochastic language models [12], and n-gram models [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since the amount of digitized music has increased enormously over the past years, the need for tools to organize, order and cluster music has increased as well. Automatic music classification has already been investigated on the basis of many different ideas, among others compression distance [2], Hidden Markov Models [1], stochastic language models [12], and n-gram models [5].…”
Section: Introductionmentioning
confidence: 99%
“…[26] examined the statistics of the chord sequences of several thousand songs, and compared the results to those from a standard natural language corpus in an attempt to find lexical units in harmony that correspond to words in language. [34,35] investigated whether stochastic language models including naive Bayes classifiers and 2-, 3-and 4-grams could be used for automatic genre classification. The models were tested on both symbolic and audio data, where an off-the-shelf chord transcription algorithm was used to convert the audio data to a symbolic representation.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a different approach is proposed to overcome those drawbacks, using a general-purpose encoding method for melodies, while music analysis is performed using language modeling, a technique that has proven to be very effective in music classification [2,8].…”
Section: Previous Work On Modeling Composer Stylementioning
confidence: 99%
“…A thorough review on the different uses of musical style in MIR tasks can be found in [9]. In a previous work [8] we used language modeling techniques to model the styles of different musical works in order to recognize their composers, with successful results. In this work we will focus on modeling the style of different composers.…”
Section: Introductionmentioning
confidence: 99%